2013
DOI: 10.12816/0001546
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Pregnancy Outcomes : Prevalence in the North of Jordan

Abstract: Objective: The aim of the study was to estimate the prevalence of the adverse pregnancy outcomes among Jordanian women. Methods: A cross sectional study was carried out in five major hospitals in the north of Jordan. Women who gave birth in the five Hospitals during the period from April to June 2007 were included in the study. Data were collected within 24 hours of delivery; the mother answered a pilot tested structured questionnaire administered by trained personnel on the maternity ward through face to face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
(14 reference statements)
1
4
1
Order By: Relevance
“…The incidence rate of preterm birth noted in this study was also lower than that reported in earlier studies in Jordan ( 7 , 9 , 10 ) . The proportion of preterm births, as reported by single-setting studies conducted in Jordan, ranged between 10.7% ( 7 ) and 12.8% ( 10 ) out of the total births in each setting, and the highest mortality in the neonatal intensive care unit was among preterm and low-birth-weight admissions ( 12 ) .…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…The incidence rate of preterm birth noted in this study was also lower than that reported in earlier studies in Jordan ( 7 , 9 , 10 ) . The proportion of preterm births, as reported by single-setting studies conducted in Jordan, ranged between 10.7% ( 7 ) and 12.8% ( 10 ) out of the total births in each setting, and the highest mortality in the neonatal intensive care unit was among preterm and low-birth-weight admissions ( 12 ) .…”
Section: Discussioncontrasting
confidence: 71%
“…The relatively lower incidence rate in this study may be due to the larger number of participants aged 20-35 years and educated participants. Evidence from previous studies indicated that young (<20 years) and advanced (≥40 years) maternal ages are strong risk factors of preterm births ( 9 , 21 , 22 ) . Similarly, increased risks of mothers having a preterm birth were associated with low or no education levels ( 21 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dubai also reported PIH and GDM as the most identi ed complications [29]. Apart from that, PTL was the most commonly observed complication in a Jordan [30]. Results from the current study indicate that participants in our group depicted sort of similar complications that are prevalent in the region.…”
Section: Resultssupporting
confidence: 50%